Cooperative learning and musical skills in university students - Pérez Mantilla , Eddy Frank (2025)
The main objective of this study is to determine the level of relationship between cooperative learning and musical skills in students of the public University of Folklore of Lima. The research is quantitative approach, correlational level, basic. The sample consisted of 87 music students from cycles II, IV, VI, VIII and X, and was selected through non-probability and intentional sampling. For the first variable, a cooperative learning scale with a reliability of 0.945 was applied and for the second variable a musical skills scale with a reliability of 0.952, the two scales were adapted. To test the hypothesis, the data have been processed using the Pearson correlation test, to determine normality, the Kolmogorov - Smirnof test was applied because the sample was larger than 50 students and for the hypothesis test, the Pearson correlation coefficient was applied. As a result, a significant correlation was found, r = 0.512, with a significance level of 0.000 (p < 0.05). This demonstrates a moderate and significant relationship between cooperative learning and the musical abilities of students at the public Folklore University of Lima.